MENDAYAGUNAKAN PENINGGALAN SEJARAH, MEWARISKAN HARMONI: KONTRUKSI MODEL HARMONI SOSIAL KEHIDUPAN MULTIETNIS MENGGUNAKAN TEKS ISTANA DALAM LOKA - Ismain, Kasimanuddin; Khakim, Moch. Nurfahrul Lukmanul (Universitas Negeri Malang, 2021)
The meaning of social harmony in the Dalam Loka Palace is reflected in the layout and architecture of multi-ethnic city. The learning model research methods include problem analysis, formulating a draft model, expert validation, model revision stage 1, limited trial of the initial model, model revision stage 2, extensive trial, final revision, and model preparation. Through validation and testing, a suitable model has been produced to foster the harmony of multiethnic life. The uniqueness of the model is the partnership of the regent as regional leader and the sultan as the holder of the Samawa tradition and culture according to the regional motto of Sabalong Samalewa. With the uniqueness of the model, it is hoped that it can eliminate the potential for conflict through the implementation of policies on internal and external factors of the model in development in the area concerned, which touches various aspects of multi-ethnic life. Makna kerukunan sosial di Keraton Dalam Loka tercermin dalam tata ruang dan arsitektur kota multietnis. Metode penelitian model pembelajaran meliputi analisis masalah, merumuskan rancangan model, validasi ahli, revisi model tahap 1, uji coba terbatas model awal, revisi model tahap 2, uji coba ekstensif, revisi akhir, dan penyusunan model. Melalui validasi dan pengujian, dihasilkan model yang cocok untuk membina kerukunan hidup multietnis. Keunikan model tersebut adalah kemitraan bupati sebagai pemimpin daerah dan sultan sebagai pemegang tradisi dan budaya Samawa sesuai semboyan daerah Sabalong Samalewa. Dengan keunikan model tersebut, diharapkan dapat menghilangkan potensi konflik, melalui penerapan kebijakan faktor internal dan eksternal model dalam pembangunan di daerah yang menyentuh berbagai aspek kehidupan multi etnis